Femtosecond laser ablation of transparent microphotonic devices and computer-generated holograms. Issue 36 (11th September 2017) - Alqurashi, Tawfiq; Montelongo, Yunuen; Penchev, Pavel; Yetisen, Ali K.; Dimov, Stefan; Butt, Haider
Abstract : Femtosecond laser ablation allows direct patterning of engineering materials in industrial settings, for the production of photonic and holographic devices. Abstract : Femtosecond laser ablation allows direct patterning of engineering materials in industrial settings without requiring multistage processes such as photolithography or electron beam lithography. However, femtosecond lasers have not been widely used to construct volumetric microphotonic devices and holograms with high reliability and cost efficiency. Here, a direct femtosecond laser writing process is developed to rapidly produce transmission 1D/2D gratings, Fresnel Zone Plate lenses, and computer-generated holograms. The optical properties including light transmission, angle-dependent resolution, and light polarization effects for the microphotonic devices have been characterized. Varying the depth of the microgratings from 400 nm to 1.5 μm allowed the control over their transmission intensity profile. The optical properties of the 1D/2D gratings were validated through a geometrical theory of diffraction model involving 2D phase modulation. The produced Fresnel lenses had transmission efficiency of ∼60% at normal incidence and they preserved the polarization of incident light. The computer-generated holograms had an average transmission efficiency of 35% over the visible spectrum. These microphotonic devices had wettability resistance of contact angle ranging from 44° to 125°. These devices can be used in a variety of applications including wavelength-selective filters, dynamic displays, fiber optics, and biomedical devices.